(untitled) (Medicine Today, 2014)
Vitiligo is an acquired skin disorder characterized by welldefined white patches that are often symmetrically distributed. The study was conducted to compare the efficacy of the combination of topical betamethasone dipropionate and calcipotriene with betamethasone dipropionate and calcipotriene alone in the treatment of localized vitiligo. A clinical trial was carried out with the patients of vitiligo from January 2012 to August 2012. In group A, 20 patients were applied betamethasone dipropionate cream 0.05% and topical calcipotriene ointment (0.005%), in group B, 20 patients were applied betamethasone dipropionate cream 0.05% only; In group C, 20 patients were applied calcipotriene ointment 0.005% alone. From base line percentage reduction of total lesion in 1st follow up in group A, group B and group C were 20%, 15% and 10% respectively. At 3rd follow up in group A, group B and group C it was 50%, 37% and 30% and at 5th follow up, it was 80%, 75% and 65% respectively. ANOVA test was done and found significant difference of reduction of total lesion of vitiligo among the groups (p< 0.05). At the completion of the study, each patient was separately graded the treated sides on a 6-point ordinal scale based on a global estimate of the change in vitiligo and found that, the very much improvement were 70%, 55% and 45%, much improvement were 20%, 30% and 35% and improvement were 10%, 15% and 20% in group A, group B and group C respectively. ANOVA test was found significant difference of success rate of patients of localized vitiligo among the groups (p value 0.005). Both the drugs, calcipotriene and betamethasone dipropionate when used individually, were found to be equally effective in the treatment of vitiligo, but the combination of the two was found to be superior in efficacy. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21310 Medicine Today 2014 Vol.26(1): 31-35